(untitled) (Journal of Asian Development Studies, 2017)
This research evaluates and indicates the issues with social networking usage and its impact on the social behavior and social interaction of youth. In this research, for getting an in-depth understanding of behavior and social interaction of youth by social media, qualitative research method through quantitative analysis is used. The research concludes that with the advent of computer technologies, world has been entered in an era of technologically rich period of time special with the wide use of social media and internet technological devices. The users of the internet are mostly college going youth of the community in Pakistan. These users are fully aware of the dangers of these technologies. They are cautious of using social media. They know how to curb the pros and cons of the social networking sites. Eventually social media is been beneficiary along rational use of it amongst youth of Pakistan.